Neuropsychological diagnostics and rehabilitation of patients with thinking disorders with brain lesions of various etiologies - Maria E. Baulina; Nataliya A. Varako; Maria S. Kovyazina; Yury P. Zinchenko; Uriy V. Mikadze; Anatoliy A. Skvortsov; Ekaterina V. Fufaeva (Национальный психологический журнал, 2020)
Background. Neuropsychological diagnosis and rehabilitation are among the fundamental practical tasks facing a clinical psychologist in accordance with applicable legal documents. The modern rehabilitation system is a partnership between patients with brain injuries, their families and various specialists involved in the rehabilitation process. Sick patients and their family continue living in the society of other people, and they have to solve issues of social interaction in a new status and with new limited opportunities. Cognitive and emotional, psychological and behavioural problems are interconnected, and neuropsychological rehabilitation should be appeal to all these problems. The Objectives of the paper are: analysing and generalization of diagnostic and rehabilitation experience accumulated in neuropsychological rehabilitation; identifying of quality criteria for neuropsychological diagnosis and rehabilitation of patients with impaired cognitive functions in brain injuries, which should be followed by a practicing clinical psychologist in the process of rehabilitation work. Results. Based on the analysis of applied research and practical guidelines, the recommended diagnostic tools for identifying thinking disorders are presented, the main directions and methods of rehabilitation work with thinking disorders that have been shown to be effective, including the organization of the dynamics of thought processes, the organization of the operational side of thinking, the organization of the regulatory side of thinking. Conclusion. The findings can sustain practical work of a clinical psychologist with patients with disturbed thinking and brain damage. The findings outline the main directions of diagnostic and rehabilitation work for the practicing psychologist.